PENERAPAN MAKE A MATCH PADA PEMBELAJARAN PKN UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Ernawati, Lina; Utami, Sri; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to describe the ability of teachers plan learning , ability of teachers to implement learning , and improved learning outcomes of students in learning by using the Citizenship Education Technique Make a Match class IV Primary School Al-Madani South East Pontianak . The method used in this research is descriptive method . The sample was 33 students . The results showed that the overall learning outcomes of the comparison cycle I to cycle II, there was an increase at an average of 73.33 into 84.55 . This shows that the study of students in learning Citizenship Education increased by using techniques Make a Match. Keywords:Learning Outcome, PKn,Make a Match